2003
DOI: 10.1086/ma.18.3585244
|View full text |Cite
|
Sign up to set email alerts
|

The Case of the Missing Productivity Growth, or Does Information Technology Explain Why Productivity Accelerated in the United States but Not in the United Kingdom?

Abstract: Accelerated in the United States but Not in the United Kingdom? 5. A long literature has, of course, explored how competition affects innovation. Aghion et al. (2002) provide recent theoretical and empirical work and suggest that over some range, greater competition raises innovation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 61 publications
5
96
0
5
Order By: Relevance
“…However, ICT investment could even be associated with initial declines in TFP as reorganization and learning require resources (Basu et al, 2003). This is also consistent with David's (1990) -delay hypothesis‖ or -learning hypothesis‖, reflecting the time taken to learn to use and apply new technologies.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…However, ICT investment could even be associated with initial declines in TFP as reorganization and learning require resources (Basu et al, 2003). This is also consistent with David's (1990) -delay hypothesis‖ or -learning hypothesis‖, reflecting the time taken to learn to use and apply new technologies.…”
supporting
confidence: 75%
“…If the diffusion of ICTs leads to subsequent complementary innovations in ICT-using industries, increasing the demand for ICT capital, then innovations in ICT production can have important long-run effects before hitting diminishing returns (Basu et al, 2003). A similar point can be made for diffusion and roll-out of broadband and ever increasing bandwidth.…”
Section: Box 5 the Role Of Ict In Us-europe Growth Differentialsmentioning
confidence: 96%
See 2 more Smart Citations
“…Many studies have actually confirmed the importance of ICTs for the improved productivity performance of the U.S. in the 1990s (Oliner andSichel, 2000 andJorgenson et al, 2002;Daveri, 2003). Similar research on individual countries has been provided for the United Kingdom (Oulton and Srinivasan, 2005;Marrano et al, 2009), but also conducted in an international comparative perspective (Basu et al, 2004;Inklaar et al, 2007;Van Ark et al, 2008). A recent study that established growth accounting as a well-tested approach is that of Jorgenson and Timmer (2011).…”
Section: Literature Reviewmentioning
confidence: 76%